Predicting rape events: The influence of intimate partner violence history, condom use resistance, and heavy drinking. Issue 1 (31st August 2020) - Gulati, Natasha K.; Stappenbeck, Cynthia A.; George, William H.; Davis, Kelly C.
Abstract: Sexual aggression perpetration is a public health epidemic, and burgeoning research aims to delineate risk factors for individuals who perpetrate completed rape. The current study investigated physical and psychological intimate partner violence (IPV) history, coercive condom use resistance (CUR), and heavy episodic drinking (HED) as prospective risk factors for rape perpetration. Young adult men ( N  = 430) ages 21–30 completed background measures as well as follow‐up assessments regarding rape events perpetrated over the course of 3 months. Negative binomial regression with log link function was utilized to examine whether these risk factors interacted to prospectively predict completed rape. There was a significant interaction between physical IPV and HED predicting completed rape; men with high HED and greater physical IPV histories perpetrated more completed rapes during follow‐up than men with low HED at the same level of physical IPV. Moreover, psychological IPV and coercive CUR interacted to predict completed rape such that men with high coercive CUR and greater psychological IPV histories perpetrated more completed rapes throughout the follow‐up period than men with low coercive CUR at the same level of psychological IPV. Findings suggest targets for intervention efforts and highlight the need to understand the topography of different forms of aggression perpetration.